Fansubs in the Context of Digital Gift Giving Culture: Puzzle Fansub Community - BAŞLAR, GÜLŞAH (ANKARA UNIV, FAC COMMUNICATION, 2019)
People gathering on networks, sharing and forming communities through new media, have caused a new conception of gift giving, called digital gift giving. Especially, significant examples of digital gift giving practices are observed in online fan communities. In Turkey the fans who are interested in animes, which are not accessible through mainstream media, use the internet to assemble online and form communities, and are involved in fansubbing practices. Within this study, the fan produced subs are seen as gifts to the community and to the anime lovers. It is aimed to understand the dynamics of digital gift giving culture through the subtitling practices of fan communities. In this article an active Puzzle Fansub community, Puzzle Fansub, is chosen as a sample. Qualitative research method is used in this article. In this context, online observations as well as in-depth interviews with the site's moderator and founder were realised. In addition, a structured online questionnaire through Google Form is used to obtain data from the users involved in content production. Within this scope 17 participants were involved in the online questionnaire.
Keywords: Fansubbing; fansub communities; gift giving; digital gift; user generated content; FANDOM